Volcano-tectonic controls of hydrothermalism on a hot spot-influenced mid-ocean ridge: Insights from Iceland and Reykjanes Ridge - Palgan, Dominik (2017)
Hydrothermal systems along mid-ocean ridges play an important role in the evolution of our planet by contributing to planetary cooling, geochemical mass balance, the formation of ore deposits and influencing the biogeography of the deep-sea ecosystems. The primary aim of this thesis was to investigate the abundance and volcano-tectonic controls of low-temperature, off-axis hydrothermal activity along the flanks of an active divergent plate boundary, initially using the subaerial Westfjords region of Iceland as a proxy. A secondary aim was to put constraints on the age of features controlling hydrothermal circulation in off-axis setting. A third aim was to postulate where hydrothermal venting along the Reykjanes Ridge may occur and determine if and where more high-temperature systems could be present. Icelandic hot springs were used as direct analogues for seafloor hydrothermal systems and results of on-land observations extrapolated to the adjacent Reykjanes Ridge. Field observations were collected in two field seasons in 2013 and 2014, mainly from the off-axis Westfjords (NW Iceland) but also from the on-axis Reykjanes Peninsula (SW Iceland). Dating of vents-hosting features was done using the 40Ar/39Ar method. The bathymetry of the northern Reykjanes Ridge was interpreted for volcano-tectonic status and hydrothermal prospecting, based on on-land observations.